Validation of an Organizational Climate Scale for the Service Sector in the Mexican Northwest - Franco Betanzos , Jonathan (Consorcio de Universidades Mexicanas A.C., 2012)
The aim of this study was to analyze the factorial structure of the Organizational Climate Scale for the service sector institutions. The participants were 116 individuals; 39 were affiliated with a health center of the Public Health Secretary, 42 with a private hospital and 35 with a hotel, all of them at Hermosillo, Sonora, México. The data were analyzed by a confirmatory factor analysis (EQS). The hypothetical model indicates three factors: organizational behavior, work stress and work organization. However, the results showed that the evaluated instrument confirmed only one fac- tor based on the dimensions of adaptation, deprivation, professional development, knowledge of functions, achievement of goals, fairness, attitude of the organization, leadership, communication and team work. thus, it is concluded that the hypothesized factorial structure does not correspond with the data. Nevertheless, the validity and reliability of the instrument was proved and it allows the evaluation of the Organizational Climate in institutions of the Services sector.